The reluctant tommy - Skirth, Ronald (Macmillan, 2010)
In April 1918, Ronald Skirth, a non-commissioned officer in the Royal Artillery, then just nineteen years old, had been sent to fight on the Western Front. This is the story of a young man who went to war a devoted servant of King and country and returned utterly convinced that war, all war, was wrong and who acted upon his convictions, making a pact with God that he would not kill. This riveting memoir was written fifty years after the end of the war, drawing on his own contemporary diary entries and letters home. Never published before, it affords a vivid, moving and surprising insight into that most dreadful of conflicts.